Enam Motivasi Mahasiswa Mengikuti Program Kampus Mengajar di Masa Pandemi Covid-19 - Zilham Usral; Alifah Beninda Desfi; Fitria Qolbina; Intan Anggraini; Renna Rofifah Sabrina (Universitas Negeri Padang, 2022)
Kampus Mengajar is part of a government program that aims to provide opportunities for students to be able to develop themselves through activities outside of lectures. This study aims to find out what is the real motivation of Padang State University students to take part in the Kampus Mengajar program during the Covid-19 pandemic. This study uses a qualitative method with a case study approach (case study design). Sources of data were taken from twenty-one informants through in-depth interviews selected using purposive sampling technique, all informants are active students who are currently/have attended the Kampus Mengajar program during the pandemic. All the results of the interviews were then analyzed through 4 stages, namely obtaining data, reducing data, presenting data and drawing conclusions. Overall, the results of the analysis found six student motivations to take part in the Kampus Mengajar program. i) one semester of lectures (20 credits) has been counted, ii) training in teaching skills, iii) gaining teaching experience, iv) building relationships, v) having intensive money and reducing the Single Tuition Fee (UKT), vi) obtaining a certificate award from the Ministry Education and Culture (Kemendikbud). The results of this study can be used as initial data for future researchers in examining this problem in different contexts and issues.